Răspunsuri

Cel mai inteligent răspuns!
2014-06-28T21:32:47+03:00
(x+1)/1+  (x+2)/2+ (x+3)/3+.....   +(x+2010)/2010 +(x+2011)/2011= 2011

x/1 + 1/1 + x/2 + 2/2 + x/3 + ......+x/2010 + 2010/2010 + x/2011+ 2011/2011 =2011

(x/1 +x/2 +x/3 + ..+x/2010+x/2011) + (1/1+2/2+3/3+...+2010/2010+2011/2011)=2011

(x * 1/1 + x* 1/2 + x* 1/3 +...+x*1/2010+ x* 1/2011) +(1+1+1....+1)=2011   (de 2011 ori 1 in a                                                                                                                           doua paranteza)

x(1+1/2+1/3+....+1/2010+1/2011) +2011=2011

x* (1+1/2+1/3+...+1/2010+1/2011)=0

x =0   daca produsul unor numere este 0 atunci se egaleaza fiecare termen cu 0 si rezulta ca x=0